EFEKTIVITAS APIUM GRAVEOLENS DALAM PEMELIHARAAN KESEHATAN REPRODUKSI DAN PENCEGAHAN HIPERTENSI LANSIA KAMPUNG KB PANGKALAN MASYHUR MEDAN JOHOR TAHUN 2025 - Lisdayanti Simanjuntak; Dina Afriani; Mastaida Tambun; Adelina Sembiring; Lisbet Gurning; Suci Rani Amalia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Hypertension is a predominant health issue in the geriatric population, contributing significantly to an increased risk of cardiovascular disease, stroke, and frailty. Major challenges in managing hypertension in the elderly include polypharmacy, declining organ function, and medication adherence. Apium graveolens (celery) contains apigenin and 3-n-butylphthalide, which are known to possess vasodilatory effects. This study aims to evaluate the effectiveness of Apium graveolens administration as a complementary therapy for the prevention and control of stage I hypertension among the elderly in a rural community setting. Methods:This study employed a Quasi-Experimental design with a Pre-test and Post-test Control Group approach, conducted in Bagun Rejo Village from January to March 2025. The subjects comprised 80 elderly individuals (aged 60 years) with grade I hypertension, selected via purposive sampling. Subjects were divided into two groups: the Intervention Group (n=40), which received a standardized dose of Apium graveolens extract for 8 weeks, and the Control Group (n=40), which received standard lifestyle education. The primary parameters measured were changes in Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP). Data analysis was performed using the Paired t-test and Independent t-test with a 95% confidence level (=0.05).Results: Baseline characteristics between the two groups were homogeneous. After 8 weeks of intervention, the Intervention Group demonstrated a significant reduction in SBP from a mean of 152.4 mmHg to 138.2 mmHg (p 0.001) and a reduction in DBP from 94.5 mmHg to 86.1 mmHg (p 0.05). Conversely, the Control Group showed no statistically significant changes. Furthermore, no significant gastrointestinal side effects or electrolyte disturbances were observed in the group consuming Apium graveolens, indicating a favorable safety profile for the elderly. Conclusion:The administration of Apium graveolens proved effective in reducing both systolic and diastolic blood pressure in elderly individuals with grade I hypertension . These findings support the potential of Apium graveolens as a safe and affordable adjuvant therapy in community-based hypertension management strategies, aiming to reduce the burden of polypharmacy in the geriatric population. Integration of this program with the Integrated Healthcare Center for the Elderly (Posyandu Lansia) is recommended for sustainability.Keywords: Apium graveolens, Geriatrics, Hypertension, Elderly, Herbal Therapy